2003
DOI: 10.1038/sj.onc.1206515
|View full text |Cite
|
Sign up to set email alerts
|

Bovine BRCA1 shows classic responses to genotoxic stress but low in vitro transcriptional activation activity

Abstract: Human BRCA1 has a genetically demonstrated role in DNA repair, and has been proposed to act as a transcriptional activator in a limited number of specialized settings. To gain insight into biologically conserved functional motifs, we isolated an ortholog of BRCA1 from cattle (Bos taurus). The predicted protein product shows 72.5% sequence identity with the human protein and conservation of amino acids involved in BRCA1 structure and function. Although the bovine C-terminus is truncated by seven amino acids as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…This panel is informative, since mouse and human BRCA1 genes share only 60% amino acid identity (40), whereas cow and dog BRCA1 are ϳ80% identical to each other and to both mouse and human proteins (39). Initially, regions homologous to amino acids 1380 -1863 of human BRCA1 were tested in the MCF7 one-hybrid assay (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This panel is informative, since mouse and human BRCA1 genes share only 60% amino acid identity (40), whereas cow and dog BRCA1 are ϳ80% identical to each other and to both mouse and human proteins (39). Initially, regions homologous to amino acids 1380 -1863 of human BRCA1 were tested in the MCF7 one-hybrid assay (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…BRCA1 from human cell extracts were identified with either Ab4 (Oncogene Research Products, San Diego, CA) or C-20 (Santa Cruz Biotechnology). BRCA1 from bovine cells was detected with C3F (39). Antisera to FCP1 were generously provided by Dr. Michael E. Dahmus (University of California, Davis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a defined system assayed in vitro, a Gal4 fusion to the carboxyl terminus of BRCA1 activates transcription, independent of other activators (9), suggesting an intrinsic transcriptional activity for BRCA1. A subsequent study found that Gal4 fusions to full-length BRCA1 could not activate transcription in transfected cells and that the degree of transcriptional activation conferred by Gal4 fusions to the carboxyl terminus of bovine BRCA1 was much lower than human BRCA1 (10). Since the human carboxyl terminus is more acidic than the bovine version, the transcriptional activity may simply be a function of its acidity.…”
mentioning
confidence: 99%
“…RT reactions were carried out using d(T) [12][13][14][15][16][17][18] (GE Healthcare) and ReverTra Ace (TOYOBO) following the manufacturer's directions. Five µg of total RNA from each sample was used as template for each reaction, and 5 µl of cDNA from each sample was used for PCR.…”
Section: Methodsmentioning
confidence: 99%